Cambio Multitemporal De La Cobertura Vegetal Y Fragmentación En La Reserva Ecológica “Mache- Chindul” Ecuador - Jose Luis Muñoz Marcillo; Marcelo Andrade Mesía; Betty González Osorio (European Scientific Journal, ESJ, 2016)
The "Mache-Chindul" -REMACH- Ecological Reserve is one of the 33 natural areas that make up the National System of Protected Areas - SNAP-, administered by the Ecuadorian government through the Ministry of Environment, MAE. This ecological reserve protects one of the few remnants of tropical dry Ecuador forest, as well as a variety of endemic species of flora and fauna, many of which are endangered, the study allowed us to determine the multitemporal cover change plant (natural forest, pasture and cultivated timberline) and fragmentation of forest area between 2002- 2012 with the implementation of programs GIS and ArcGIS Desktop 9.3 Er Mapper. Information of the study area was lifted from satellite Landsat 7 ETM (spatial resolution 30 m per pixel) to the same as a composition of pseudo color (RGB-431) and a classification applied supervised using the method of Minimum Distance. The ecological reserve has an area of 53,662 hectares of natural forest, equivalent to 44.7 % of total area, 23.1 % is regeneration or recovery of natural forest with an area of 27,707 hectares; the natural forest has undergone several interventions, considering the most affected and the peripheral area south of the rivet end, fragmentation was of 38,632 was equivalent to 32.2 % of the total area of the reserve, in the category of cultivated grass product the increase of the agricultural frontier and decreasing natural forest cover from the illegal extraction of wood, also the pressure from timber companies and colonization fronts, concerning the population index this has decreased from 5.71 to 5.39 hab / km2.